Influence of new media use on patients' healthcare-seeking behavior - Yu LEI (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the status of new media dependence and healthcare-seeking behavior among patients and to explore the influence and mechanism of new media use on the patients' healthcare-seeking behavior. Methods Totally 526 patients were randomly recruited at 22 medical institutions of various levels in urban Shanghai during January 11 - 24, 2018 for an online survey. A self-designed questionnaire was used to collect information on demographics, social support, self-efficacy, new media use, and healthcare-seeking attitude/behavior. A media dependency theory- and the theory of planned behavior-based structural equation model was adopted in analysis on the relationship between new media use and healthcare-seeking behavior. ResultsFor the 526 respondents with complete information, the patients' dependence on new media was at an average level but the patients' healthcare-seeking behavior was good. Based on the established structural equation model with good fitting indicators, new media dependence is positively correlated with personal healthcare-seeking attitude (β = 0.50, P < 0.01); healthcare-seeking attitude positively affects healthcare-seeking intention (β = 0.78, P < 0.01) and indirectly affects healthcare-seeking behavior (β = 0.50, P < 0.01); however, new media dependence is not related to self-efficacy (β = - 0.19, P = 0.07) and social support (β = 0.15, P = 0.26); in addition, self-efficacy positively affects (β = 0.14, P = 0.03) healthcare-seeking intention and directly and indirectly affects healthcare-seeking behavior. ConclusionAs a tool and channel of health communication, new media is of significant potential and practicability in the intervention on healthcare-seeking behavior among urban hospital attendees.